The terms used by al-Khalil ibn Ahmad on the description of the Arab. - Kydyrbayev., K. A.; Mustafayeva., A. A.; Inayatulla., M. (Journal of Oriental Studies, 2016)
This article discusses the terms used by al-Khalil Ibn Ahmad the Arab sounds on the description, as well as reveals their values.